PERMITTIVITY RESEARCH OF BIOLOGICAL SOLUTIONS IN GIGAHERTZ FREQUENCY RANGE - Anton S. Demin (Naučno-tehničeskij Vestnik Informacionnyh Tehnologij, Mehaniki i Optiki, 2017)
Subject of Research. We present results of permittivity research in gigahertz frequency range for saline and glucose solutions used in medical practice. Experiment results are substantiated theoretically on the basis of Debye-Cole model. Method. Researches have been carried out on blood plasma of healthy donor, water, normal saline and glucose solutions with different concentration from 3 to 12 mmol/l. Experiments have been performed by an active nearfield method based on measuring the impedance of a plane air-liquid boundary with open end of coaxial waveguide in the frequency range from 1 to 12 GHz. Measurement results have been processed with the use of vector analyzer computer system from Rohde & Schwarz. Transmittance spectra have been determined by means of IR-spectrometer from TENZOR-Bruker. Main Results. Simulation results have shown good agreement between the experimental results and the model, as well as the choice of the main parameters of the Debye-Cole model in the studied frequency range for all media. It has been shown that the range of 3-6 GHz can be considered as the main one in the development of diagnostic sensors for the non-invasive analysis of the glucose concentration in the human blood. Practical Relevance. Electrodynamic models of test fluid replacing human blood give the possibility to simulate the sensor basic characteristics for qualitative and quantitative estimation of glucose concentration in human blood and can be used to create an experimental sample of a non- invasive glucometer.